Breve notícia da recente erupção na ilha do Fogo e suas consequências - Correia, Ezequiel; Costa, Fernando (Finisterra, 1995)
BRIEF NOTES ABOUT THE RECENT VOLCANIC ERUPTION AT FOGO ISLAND - This article provides a concise description of the volcanic eruption that occurred in 1995 in the island of Fogo (Cape Verde). It focuses on the evolution of the eruption, its characteristics, and the alteration it produced on the topography and morphology of the landscape of Chã das Caldeiras. The consequences of this phenomenon on the human and agricultural occupation are also emphasized.